2018
DOI: 10.1093/milmed/usx085
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Exertional Heat Illnesses Associated with Sickle Cell Trait in U.S. Military

Abstract: Our findings suggest that SCT screening will identify approximately a third of SCT individuals at risk for EHI, but does not provide definitive evidence for universal compared with selective (e.g., occupational based) in military enlistees. A cost-effectiveness analysis is needed for policy makers to assess the overall value of universal SCT screening to prevent morbidity and mortality in both the military and the collegiate athletic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The titles and abstracts were screened, and 1502 articles excluded, leaving 154 articles for full-text review. Data in Table S2 depict that 41 articles were included in the review [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], comprising 29 descriptive and cross-sectional studies [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The titles and abstracts were screened, and 1502 articles excluded, leaving 154 articles for full-text review. Data in Table S2 depict that 41 articles were included in the review [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], comprising 29 descriptive and cross-sectional studies [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…Younger age was identified as a potential risk factor in nine studies ( Box 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, the findings from six (6) studies which assessed the relationship between EHI and age were inconsistent [ 33 , 34 , 49 , 50 , 53 , 57 ]. While one study reported that younger people had an increased risk [ 50 ], another study reported that older people had an increased risk of EHI [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have attempted to capture the potential risk factors implicated in heat illness. Commonly cited precipitants include: alcohol (Armstrong et al, 2007), medications (Epstein, 1990;Armstrong et al, 2007) (particularly psychiatric), recreational drugs (Epstein et al, 1999;Armstrong et al, 2007), sickle cell trait (Nelson et al, 2017;Singer et al, 2018), recent febrile illness/diarrheal illness (Epstein, 1990;Armstrong et al, 2007), sleep deprivation (Armstrong et al, 1990(Armstrong et al, , 2007Bolton et al, 2006;Stacey et al, 2015), sunburn (Armstrong et al, 2007), obesity (Gardner et al, 1996;Epstein et al, 1999;Wallace et al, 2006;Bedno et al, 2014), dehydration (Montain et al, 1998;Armstrong et al, 2007) as well as the known intrinsic factors such as environmental temperature and humidity, clothing and activity levels (Kark et al, 1996;Howe and Boden, 2007). More militarily relevant studies have associated the increased risk of prior heat stroke (Armstrong et al, 2007), combat or healthcare occupational roles, reservists (Bricknell, 1996), subjects over 30 (Epstein, 1990), female sex (Fortney and Senay, 1979;Carter et al, 2005), lower levels of physical fitness (Shvartz et al, 1977b;Epstein, 1990;Gardner et al, 1996;Wallace et al, 2006;Bedno et al, 2014), lack of acclimatization (Epstein, 1990;Bricknell, 1996;Armstrong et al, ...…”
Section: Practices and Pitfalls In Generating And Sustaining Heat Adamentioning
confidence: 99%